Optimizing Cancer Care Delivery through Implementation Science - Adesoye, Taiwo; Greenberg, Caprice C.; Neuman, Heather B. (Frontiers in Oncology, 2016)
The 2013 Institute of Medicine report investigating cancer care concluded that the cancer care delivery system is in crisis due to an increased demand for care, increasing complexity of treatment, decreasing work force, and rising costs. Engaging patients and incorporating evidence-based care into routine clinical practice are essential components of a high-quality cancer delivery system. However, a gap currently exists between the identification of beneficial research findings and the application in clinical practice. Implementation research strives to address this gap. In this review, we discuss key components of high-quality implementation research. We then apply these concepts to a current cancer care delivery challenge in women’s health, specifically the implementation of a surgery decision aid for women newly diagnosed with breast cancer.